Direct glycosylation of unprotected and unactivated sugars using bismuth nitrate pentahydrate - Polanki, Innaiah K.; Kurma, Siva H.; Bhattacharya, Asish K. (Journal of Carbohydrate Chemistry, 2015)
Bi(NO3)(3), a low-cost, mild, and environmentally green catalyst, has been successfully utilized for Fischer glycosylation for the synthesis of alkyl/aryl glycopyranosides by reacting unprotected sugars, namely, D-glucose, L-rhamnose, D-galactose, D-arabinose, and N-acetyl-D-glucosamine with various alcohols in good to excellent yields. The glycosides were formed with high alpha-selectivity. Further, an expedient separation of alpha- and beta-glycosides using silver nitrate-impregnated silica gel flash liquid chromatography has been developed.
Keywords: Bismuth nitrate; carbohydrates; Fischer glycosylation; Flash chromatography; Separation